Navigating Hyperkalaemia- The A-to-H Clinical Strategy - Sourabh Sharma; Sanjay Kalra (Journal of the Pakistan Medical Association, 2024)
Hyperkalaemia is a life-threatening dyselectrolytaemia which is characterized by elevated serum potassium levels. It needs a systematic and overarching approach to effectively manage a case of hyperkalaemia. We propose a structured A-to-H approach to guide clinicians in managing hyperkalaemia, ensuring that no critical aspect is neglected or inadvertently missed. This approach involves Analytical accuracy, Background, Clinical context, Diagnosis and drugs, Evaluation, Follow-up, Guidelines adherence, and Health education. With this article, we reiterate the need to properly assess and promptly manage a case of hyperkalaemia in various clinical settings, providing detailed explanation of each component of the ABCDEFGH approach. Keywords: Hyperkalaemia, Potassium, Potassium binders, Prevention, Health evaluation.